Pengaruh Motivasi pada Penilaian Prestasi Kerja Karyawan PT. INHUTANI II Kotabaru Kalimantan Selatan - Efrianti, Kumara (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2019)
This research discuses about motivatin of staff PT. INHUTANI II Kota Baru Kalimantan Selatan the objective of this research is to analyze the influence of physic need variables (X1), safety need (X2), social need (X3), appreciation need (X4), self actualizing need (X5). The motivation is defined as the personal condition of someone backing up the individual willing to do particular activities for reaching a purpose. In order someone being able to be motivated to do something, it need to know the weakness inside the individual that is need. From the resesarch simultaneously affect the motivation and partially take effect significant on employee performance staf PT. INHUTANI II Kota Baru kalimantan Selatan with sign 0,000 and correlation coefficient between 0,41 to 0,60 are included in the category being and accompanied by significance (sig) 0,000 < 0,01.